Modeling of some nonstationary processes in tokamak plasmas - Borisov, M.A.; Cherkasov, S.V.; Danilov, A.V.; Dnestrovskij, Yu.N.; Dnestrovskij, A.Yu.; Field, A.; Lysenko, S.E.; Meyer, H.; Vershkov, V.A. (Вопросы атомной науки и техники, 2013)
The results of modeling of shots from two series of experiments in two tokamaks with rather different geometric parameters are presented. The first one includes two shots from the spherical tokamak MAST with current ramp up, and the second one, a number of T-10 shots with periodic gas puffing. The modeling was performed with the ASTRA code in the framework of Canonical Profiles Transport Model (CPTM).